GEO-6: Global Environment Outlook: Regional assessment for North America - United Nations Environment Programme (United Nations Environment Programme, 2016)
The sixth Global Environment Outlook (GEO-6) Regional Assessment for North America paints a comprehensive picture of the environmental factors contributing to human health and well-being at the regional level. Backed by a largebodyofrecent,crediblescientificevidence,regional-wide consultations and a robust intergovernmental process, the assessment demonstrates that regional and global multilateral environmental agreements have improved environmental conditions in North America.